2023
DOI: 10.1007/s13300-023-01468-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Therapy for the Management of Diabetes Mellitus: A Narrative Review of Innovative Treatment Strategies

Ken M. Nkonge,
Dennis K. Nkonge,
Teresa N. Nkonge

Abstract: The discovery of insulin was presented to the international medical community on May 3, 1922. Since then, insulin has become one of the most effective pharmacological agents used to treat type 1 and type 2 diabetes mellitus. However, the initiation and intensification of insulin therapy is often delayed in people living with type 2 diabetes due to numerous challenges associated with daily subcutaneous administration. Reducing the frequency of injections, using insulin pens instead of syringes and vials, simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Additionally, it aids in storing excess glucose in the liver for future use, contributing to maintaining blood sugar levels within a healthy range. [96], [97], [98], [99], [100] Pancreatic enzymes constitute a cluster of digestive enzymes crucial for breaking down food in the digestive system. While not commonly employed as a direct treatment for pancreatic cancer, they find utility in managing symptoms associated with pancreatic insufficiency resulting from pancreatic diseases or treatments.…”
Section: Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it aids in storing excess glucose in the liver for future use, contributing to maintaining blood sugar levels within a healthy range. [96], [97], [98], [99], [100] Pancreatic enzymes constitute a cluster of digestive enzymes crucial for breaking down food in the digestive system. While not commonly employed as a direct treatment for pancreatic cancer, they find utility in managing symptoms associated with pancreatic insufficiency resulting from pancreatic diseases or treatments.…”
Section: Targeted Therapymentioning
confidence: 99%
“…Additionally, it aids in storing excess glucose in the liver for future use, contributing to maintaining blood sugar levels within a healthy range. [96], [97], [98], [99], [100]…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these products have been translated into therapeutic practice, mainly due to their slow reaction to increases in glucose, meaning that, today, only two molecules have been tested in humans. The main characteristics that a glucose-sensitive insulin must show in order to be transferred to clinical practice are the selective detection of glycemia, no toxicity or side effects, responsiveness to physiological glycemic ranges, and a quick and efficient reaction, reversible in the case of glucose changes [ 51 , 53 ]. Although to date there has been no molecule found that is capable of meeting all these characteristics, there are several pharmaceutical laboratories that are committed to this line of research.…”
Section: The Future Of Insulin Therapymentioning
confidence: 99%
“…The first non-injectable insulin administration method to hit the market was inhaled insulin, marketed in 2006 by Pfizer under the name Exubera; however, it was quickly withdrawn from the market due to its adverse effects, mainly coughing and alterations of lung function [ 53 , 54 ]. Over the years, new formulations have come to the market, and although none have yet been able to replace injectable insulin, several inhaled insulins are in the clinical trial phase, and seek to establish themselves as a real alternative to injectable insulin in clinical practice.…”
Section: The Future Of Insulin Therapymentioning
confidence: 99%